Enhancement of journalistic skills and web management based on AIK for Muhammadiyah Cadres in Daerah Istimewa Yogyakarta - Fadillah , Dani; Kurniawan, Afan; Tarmuji, Ali; Rahman, Arif; Nugroho, Rhomandika Cahyo; Juwanti, Juwanti; Safani, Affan; Sucipto, Sucipto; Seruni, Dewi; Latifah, Umi; Arifin, Damaya Noor; Nurrahmah, Nugrahini; Ardiansyah, Anggito Setiawan (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
This paper aims to describe how the Council for Libraries and Information of the Regional Leadership of Muhammadiyah in the Special Region of Yogyakarta (MPI PWM DIY) organized a cadre journalism school to equip Muhammadiyah cadres and administrators in the Muhammadiyah organization in Yogyakarta with journalistic skills aligned with the values of Al-Islam and Muhammadiyah (AIK). The training was conducted in a workshop format, where participants were provided with ideal academic writing techniques and then introduced to AIK-standard journalistic principles. Subsequently, participants were guided to produce journalistic scripts ready for publication in the Muhammadiyah DIY-affiliated news media.